European cooperation and Workers’ sports (Fiep Bulletin - online, 2015)
Created in 1949, the council of Europe which has its head-quarters in Strasbourg (France), is the largest political institution in Europe. It Numbers 18 member-countries at present, stretching from Iceland to Turkey, and its activities affect some 300 million Europeans.